Physicochemical changes and sensory characterization of a balsamic vinegar dressing at different °brix - Chirife, Jorge (2009)
Fil: Chirife, Jorge. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina